Effective electrocatalytic methanol oxidation of Pd-based metallic glass nanofilms. Issue 44 (2nd November 2020) - Sarac, Baran; Karazehir, Tolga; Ivanov, Yurii P.; Putz, Barbara; Greer, A. Lindsay; Sarac, A. Sezai; Eckert, Jürgen
Abstract : Compared to conventional polycrystalline Pd, Pd79 Au9 Si12  metallic glass nanofilm electrocatalyst offers better methanol oxidation in alkaline medium, CO poisoning tolerance and catalyst stability even at high scan rates or high methanol concentrations. Abstract : Compared to their conventional polycrystalline Pd counterparts, Pd79 Au9 Si12 (at%) – metallic glass (MG) nanofilm (NF) electrocatalysts offer better methanol oxidation reaction (MOR) in alkaline medium, CO poisoning tolerance and catalyst stability even at high scan rates or high methanol concentrations owing to their amorphous structure without grain boundaries. This study evaluates the influence of scan rate and methanol concentration by cyclic voltammetry, frequency-dependent electrochemical impedance spectroscopy and a related equivalent circuit model at different potentials in Pd–Au–Si amorphous NFs. Structural and compositional differences for the NFs are assessed by high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM), energy dispersive X-ray (EDX) mapping and X-ray diffraction (XRD). The ratio of the forward to reverse peak current density i pf / i pb for the MG NFs is ∼2.2 times higher than for polycrystalline Pd NFs, evidencing better oxidation of methanol to carbon dioxide in the forward scan and less poisoning of the electrocatalysts by carbonaceous ( e.g. CO, HCO) species. Moreover, the electrochemical circuit model obtained from EIS measurements reveals that the MOR occurring around −100 mV increases the capacitance without any significant change in oxidation resistance, whereas CO2 formation towards lower potentials results in a sharp increase in the capacitance of the Faradaic MOR at the catalyst interface and a slight decrease in the corresponding resistance. These results, together with the high i pf / i pb = 3.37 yielding the minimum amount of carbonaceous species deposited on the thin film during cyclic voltammetry and stability in the alkaline environment, can potentially make these amorphous thin films potential candidates for fuel-cell applications.